Exploring Student Speaking Anxiety in EFL Classrooms: Causes, Effects, and Strategies for Alleviation A Case Study of the First-Semester Students at Al-Swani Faculty of Arts, University of Tripoli (Comprehensive Journal of Science, 2026)
This study investigates the causes, effects, and potential strategies for reducing speaking anxiety among first-semester EFL students at Al-Swani Faculty of Arts, University of Tripoli. Using a descriptive analytical method, data were collected through a structured questionnaire and classroom observation checklist. The results revealed that speaking anxiety is highly prevalent among beginners, mainly due to fear of making mistakes, limited vocabulary, low confidence, and concerns about negative evaluation. Anxiety was found to negatively influence students’ oral performance, leading to reduced participation, hesitation, physical symptoms, and avoidance behaviors. However, the findings also showed that supportive teacher behavior, sufficient preparation time, and collaborative speaking tasks can effectively reduce anxiety. The study concludes that addressing psychological and classroom-related factors is essential for improving learners’ oral communication and offers a set of practical recommendations for teachers and institutions.
Keywords: speaking anxiety, EFL learners, classroom observation, foreign language anxiety, oral performance